2014
DOI: 10.3109/17453674.2014.913955
|View full text |Cite
|
Sign up to set email alerts
|

How precise is the PRECICE compared to the ISKD in intramedullary limb lengthening?

Abstract: Background and purposeThe PRECICE intramedullary limb lengthening system uses a new technique with a magnetic rod and a motorized external remote controller (ERC) with rotational magnetic field. We evaluated the reliability and safety of the PRECICE system.MethodsWe compared our preliminary results with PRECICE in 24 patients (26 nails) with the known difficulties in the use of mechanical lengthening devices such as the ISKD. We used the Paley classification for evaluation of problems, obstacles, and complicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
80
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(97 citation statements)
references
References 11 publications
(17 reference statements)
11
80
1
5
Order By: Relevance
“…Driving mechanisms are not expected to function properly in individuals with a body mass index >35. Wide soft tissue interval >5-7 cm may interfere with external remote controller function of the PRECICE magnetically motorised nail [23].…”
Section: Contraindicationsmentioning
confidence: 99%
“…Driving mechanisms are not expected to function properly in individuals with a body mass index >35. Wide soft tissue interval >5-7 cm may interfere with external remote controller function of the PRECICE magnetically motorised nail [23].…”
Section: Contraindicationsmentioning
confidence: 99%
“…11,19 In none of the previous studies or in the current study did any of the patients experience intolerable pain during distraction, as no external or painful rotational manipulation of the limbs was required. 19 In a previous study done by Kirane et al (2014), momentary loss of limb ROM was observed in various patients after surgery, and the original ROM recovered within a few months after surgery. 11 This was not the case in the current study, as none of the patients experienced temporary loss of ROM in the limbs.…”
Section: Discussionmentioning
confidence: 99%
“…11,19 In previous cases the nail distraction failure also occurred (non-functional magnet mechanism), in which case the nail was replaced and distraction was successfully continued. 11,19 In none of the previous studies or in the current study did any of the patients experience intolerable pain during distraction, as no external or painful rotational manipulation of the limbs was required.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations